The Performance Variable of the Actor's Techniques in Postmodern Theater Shows: وئام وافي علي (Al-Academy, 2019)
The postmodern ideas and concepts have produced social, political and economic variables that have been affected by wars, crises, the role of globalization and the information revolution. They have created many variables in concepts and great variables in technological, artistic and cultural innovations. All these changes have contributed to changing the form of the theatrical show aesthetically and intellectually, which cast a shadow over the nature of the actor's performance who has become more demanding to change his performance and to find the mechanisms and new nature of work governing him corresponding to those variables and this prompted the researcher to adopt the subject (the performance variable of the actor's techniques in postmodern theatre show (. Research importance:It provides benefit to actors, directors and workers in the field of theater. The researcher in the theoretical framework tackled two sections:The first section: Postmodern conceptThe second section: the actor's performance in postmodernismThe researcher chose a sample for the analysis represented by the play (Azaiza), which was presented in 2014, and after the analysis, a set of results have been found and the most important of which are:- The theory of playing in the performance and performance technology clearly contributed to the blending of all the styles and artistic trends within one center that depends through their way on fragmentation, anarchy, contradiction, and the ambiguity and multiplicity of the meaning. Then the conclusions reached at and the most important of which are:-The performance variable of the actor's techniques is highlighted in postmodern presentations via subjugating the actor to the hegemony of the techniques that made him a sign subject to its authority within the show system.